Multiscale Combinatorial Grouping - Arbelaez, Pablo; Pont-Tuset, Jordi; Barron, Jon; Marques, Ferran; Malik, Jitendra (2014 IEEE Conference on Computer Vision and Pattern Recognition, 2014)
We propose a unified approach for bottom-up hierarchical image segmentation and object candidate generation for recognition, called Multiscale Combinatorial Grouping (MCG). For this purpose, we first develop a fast normalized cuts algorithm. We then propose a high-performance hierarchical segmenter that makes effective use of multiscale information. Finally, we propose a grouping strategy that combines our multiscale regions into highly-accurate object candidates by exploring efficiently their combinatorial space. We conduct extensive experiments on both the BSDS500 and on the PASCAL 2012 segmentation datasets, showing that MCG produces state-of-the-art contours, hierarchical regions and object candidates.